Piano Sonatas appassionata, moon light - Beethoven, Ludwig van. 1770-1827
1.- Sonata No 14 in C sharp minor, "Moonlight" 2.- Sonata No 23 in F minor "Appassionata" 3.- Sonata No 26 in E flat major "Les adieux"